2023
DOI: 10.26668/businessreview/2023.v8i5.1511
|View full text |Cite
|
Sign up to set email alerts
|

Improving Firm Sustainability Through Dynamic Capability: The Mediation Role of Ambidexterity

Abstract: Purpose: This study aims to analyze the effect of dynamic capability dimensions on sustainability and ambidexterity. Furthermore, this study also analyzes the mediating role of ambidexterity to influence sensing, seizing and reconfiguring capabilities in building firm sustainability.   Theoretical framework:  There are inconsistencies in previous research related to the effect of dynamic capability. Some recent literatures emphasize the important role of dynamic capability in increasing company sustainability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Several growth models are found in the literature, such as the models of Gompertz (1825); Richards (1959); Stannard et al, (1985); Polese et al, (2011); Bhatia et al, (Bhatia et al, 2011); Erbas et al, (2014); Kim et al, (Kim et al, 2018) and the logistic model Razanamahandry et al, (Razanamahandry et al, 2018); Chen et al, (2020) and others by Choi & Seo (2018); Sreenivas et al, (2020); Łobacz et al, (2022). Models are abstractions of reality; in fact, they can all be considered essential to capture different scales of a phenomenon and to better understand the dynamics of an ecosystem (Hadi, 2023;Pinto & Shimakawa, 2022;A Succurro et al, 2017;Antonella Succurro & Ebenhöh, 2018). On the one hand, there are models with deterministic approaches (based on differential equations and stoichiometric models with constraints) and, on the other hand, models with stochastic approaches (associated with a cumulative distribution function and a probability density function).…”
Section: Theoretical Referentialmentioning
confidence: 99%
“…Several growth models are found in the literature, such as the models of Gompertz (1825); Richards (1959); Stannard et al, (1985); Polese et al, (2011); Bhatia et al, (Bhatia et al, 2011); Erbas et al, (2014); Kim et al, (Kim et al, 2018) and the logistic model Razanamahandry et al, (Razanamahandry et al, 2018); Chen et al, (2020) and others by Choi & Seo (2018); Sreenivas et al, (2020); Łobacz et al, (2022). Models are abstractions of reality; in fact, they can all be considered essential to capture different scales of a phenomenon and to better understand the dynamics of an ecosystem (Hadi, 2023;Pinto & Shimakawa, 2022;A Succurro et al, 2017;Antonella Succurro & Ebenhöh, 2018). On the one hand, there are models with deterministic approaches (based on differential equations and stoichiometric models with constraints) and, on the other hand, models with stochastic approaches (associated with a cumulative distribution function and a probability density function).…”
Section: Theoretical Referentialmentioning
confidence: 99%
“…The existing research study on eco-friendly entrepreneurs identified a research gap that this TBL theoretical study fills. The inconsistent effects of dynamic capability on the sustainability of SHG women entrepreneurs will be examined in relation to the support (Hadi, 2023).…”
Section: Introductionmentioning
confidence: 99%